2019
DOI: 10.1371/journal.pone.0216104
|View full text |Cite
|
Sign up to set email alerts
|

Beta-caryophyllene enhances wound healing through multiple routes

Abstract: Beta-caryophyllene is an odoriferous bicyclic sesquiterpene found in various herbs and spices. Recently, it was found that beta-caryophyllene is a ligand of the cannabinoid receptor 2 (CB2). Activation of CB2 will decrease pain, a major signal for inflammatory responses. We hypothesized that beta-caryophyllene can affect wound healing by decreasing inflammation. Here we show that cutaneous wounds of mice treated with beta-caryophyllene had enhanced re-epithelialization. The treated tissue showed increased cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 91 publications
1
71
0
Order By: Relevance
“…As β-caryophyllene activates several different types of receptors other than olfactory receptors, the impact on improving re-epithelialization can be mediated by activating other routes. In these studies [2], although β-caryophyllene is known as a cannabinoid receptor 2 (CB2) ligand [5], the CB2 gene was down-regulated in skin 17 h post-injury+β-caryophyllene-application, whereas transient receptor potential cation channel subfamily melastatin (TRPM1, TRPM6), and transient receptor potential cation channel subfamily vanilloid (TRPV4, TRPV6) were significantly up-regulated [2]. This suggests the possibility of the involvement of these channels in improving wound healing.…”
Section: The Skinmentioning
confidence: 95%
See 4 more Smart Citations
“…As β-caryophyllene activates several different types of receptors other than olfactory receptors, the impact on improving re-epithelialization can be mediated by activating other routes. In these studies [2], although β-caryophyllene is known as a cannabinoid receptor 2 (CB2) ligand [5], the CB2 gene was down-regulated in skin 17 h post-injury+β-caryophyllene-application, whereas transient receptor potential cation channel subfamily melastatin (TRPM1, TRPM6), and transient receptor potential cation channel subfamily vanilloid (TRPV4, TRPV6) were significantly up-regulated [2]. This suggests the possibility of the involvement of these channels in improving wound healing.…”
Section: The Skinmentioning
confidence: 95%
“…Studies using mice have found that the essential oil of oleoresin, Copaifera paupera, which contains β-caryophyllene, improves wound healing [68], although it was not clear in that study whether β-caryophyllene produced the impact nor whether an olfactory receptor was involved. Studies using β-caryophyllene (and not essential oils that contain β-caryophyllene) have shown that, topical application of β-caryophyllene on cutaneous wounds can improve re-epithelialization, but the olfactory system was not involved in the impact [2]. As β-caryophyllene activates several different types of receptors other than olfactory receptors, the impact on improving re-epithelialization can be mediated by activating other routes.…”
Section: The Skinmentioning
confidence: 99%
See 3 more Smart Citations